2015
DOI: 10.1371/journal.pone.0126485
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Spontaneous Square-Wave Jerks in the Healthy Macaque Monkey during Visual Fixation

Abstract: Saccadic intrusions (SIs), predominantly horizontal saccades that interrupt accurate fixation, include square-wave jerks (SWJs; the most common type of SI), which consist of an initial saccade away from the fixation target followed, after a short delay, by a return saccade that brings the eye back onto target. SWJs are present in most human subjects, but are prominent by their increased frequency and size in certain parkinsonian disorders and in recessive, hereditary spinocerebellar ataxias. SWJs have been als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(56 reference statements)
2
6
0
Order By: Relevance
“…In line with earlier experimental observations in monkey V1 [ 21 , 22 , 27 , 53 , 72 , 101 ], we observed the quasiperiodic occurrence (every 200–500 ms) of MSs during normal awake visual processing. They continuously modulated visual neuronal processing and prohibited the network dynamics from reaching an equilibrium state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with earlier experimental observations in monkey V1 [ 21 , 22 , 27 , 53 , 72 , 101 ], we observed the quasiperiodic occurrence (every 200–500 ms) of MSs during normal awake visual processing. They continuously modulated visual neuronal processing and prohibited the network dynamics from reaching an equilibrium state.…”
Section: Discussionsupporting
confidence: 92%
“…Recent work has shown that MSs, in tandem with drifts, have important implications for transforming visual spatial information into temporal modulations [ 35 , 36 , 50 , 51 , 101 ]. MSs induce transient modulations that relate to lower- and high-frequency content of the visual image, whereas drifts lead to temporal modulations related mainly to higher-frequency (more local) content.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to an increase in the number of microsaccades made toward and away from the peripheral target stimulus, as has been reported in previous studies of covert attention ( Engbert & Kliegl, 2003 ; Laubrock et al, 2005 ; Rolfs, Engbert, & Kliegl, 2004 ). Alternatively, this result may simply reflect that fact the microsaccades tend to be horizontal ( Costela et al, 2015 ) and that a larger proportion of horizontal microsaccades may occur as fixation stability decreases.…”
Section: Discussionmentioning
confidence: 99%
“…Standard sterile surgical techniques, recording procedures, and animal care methods were approved by the Institutional Animal Care and Use Committee at Barrow Neurological Institute. Information about the breeding, care, and maintenance of the macaques can be found in previously reported studies that addressed different experimental questions (Costela et al, 2015 ; Costela et al, 2014 ). Prior to the eye movement recordings, cranial head-post and scleral search-coil implantation surgeries were conducted, under general anesthesia using aseptic techniques, and with full postoperative analgesia and antibiotic therapy.…”
Section: Methodsmentioning
confidence: 99%